EFFECT OF LENDING PT. BPR MITRA DHANACESWARA TO INCREASE REVENUES TRADER SMALL AND MICRO (Case Study in PT. BPR Mitra Dhanaceswara) - Aulady, Rizky; Ekowati, Wiwik Hidajah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Bank is a financial institution whose principal business is to collect funds and distribute those funds back into the community in the form of credit and to provide services in payment traffic and circulation. To facilitate its operations, the bank established a branch in the areas with the aim of providing bank services to the community, especially in economically weak. One of the services performed by the bank is lending to the public. Basically the main function of the credit is to the fulfillment services to the needs of the community (to service the society) in order to encourage and expedite trade, production and services even consumption, all of it aimed to improve human life. This study aims to determine whether there is the effect of giving loans against income traders BPR micro and small enterprises. This research method using kuantitatif descriptive case study approach. Having found trader revenues and results obtained after borrowing money at BPR it will be calculated to find out whether there is the effect of giving loans against income traders BPR micro and small enterprises. This calculation itself will be using 4 methods, namely, regression, product moment correlation, T test and F test Keywords: Income, Credit, BPR